Breeding of Philemon buceroides by Synchronization of Pregnant Mare Serum Gonadotropine (PMSG) Reproductive Hormone and Estrogen as Conservation for Preventing Its Extinction - M Yamin; Khairuddin Khairuddin; Padusung Padusung (Jurnal Penelitian Pendidikan IPA, 2022)
The research aims to figure out how to breed Philemon buceroides in captivity and make recommendations for conservation activities in-situ and ex-situ. Philemon buceroides are bred by giving the Pregnant Mare Serum Godadotrophin (PMSG) and Estrogen hormones and artificial insemination to birds who are sexually mature and physically healthy at least one year old. The birds in this study were Philemon buceroides that had been reared for at least a year to lessen stress. According to the researchers, the Philemon buceroides sample was acclimatized for 7 days in each birdcage. The treatment group was superovulated the next day to produce more eggs than normal, using PMSG hormone at a dose of 150 ImÂ in 10 milliliters of ferologic Nacl / Kg BW once a day for three days. Only 10 milliliters of ferologic NaCl were given orally to the control group. The following day, lust/Estrus synchronization was performed utilizing the Estrogen hormone at a dose of 150 ImÂ in 10 milliliters of ferological NaCl orally once a day for three days. Sperm was taken from male Philemon buceroides. As a result, synchronizing the reproductive hormones Pregnant Mare Serum Gonadotrophin (PMSG) and Estrogen in male and female Philemon buceroides considerably influenced the increase in ovulation, however the eggs generated by the mother Philemon buceroides have yet to produce chicks. Furthermore, obtaining male sperm is challenging. Just one sperm pulled out one drop from the three guys, while the other two did not